2009
DOI: 10.1007/s12011-009-8366-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Betaine on Changes in the Levels of Membrane-bound ATPase activity and Mineral Status in Experimentally Induced Myocardial Infarction in Wistar Rats

Abstract: Cardiovascular diseases are emerging as a major public health problem in most parts of the world even in developing countries still afflicted by infectious diseases, undernutrition, and other illnesses related to poverty. In the present study, we investigated the protective effect of betaine, a potent lipotropic molecule, on changes in the levels of membrane-bound ATPase activities, lipid peroxidation, sulfhydryl activities, and mineral status in isoprenaline-induced myocardial infarction in Wistar rats, an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Earlier, we reported the protective effect of betaine on mitochondrial function (Ganesan et al 2007a) protein and glycoprotein metabolism (Ganesan et al 2007b) and lipid metabolism (Ganesan et al 2008) and lysosomal function (Ganesan and Anandan 2009) against isoprenaline-induced myocardial infarction in rats. In the present study, an attempt was made to assess the protective effects of betaine against oxidative damage during experimentally induced restraint stress in Wistar albino rats with respect to changes in the levels of lipid peroxidation, antioxidant status (GST, GPx, CAT, SOD activities, and GSH level) in lymphoid organs of thymus and spleen, changes in the adrenal weight, plasma protein, and corticosterone levels.…”
Section: Introductionmentioning
confidence: 94%
“…Earlier, we reported the protective effect of betaine on mitochondrial function (Ganesan et al 2007a) protein and glycoprotein metabolism (Ganesan et al 2007b) and lipid metabolism (Ganesan et al 2008) and lysosomal function (Ganesan and Anandan 2009) against isoprenaline-induced myocardial infarction in rats. In the present study, an attempt was made to assess the protective effects of betaine against oxidative damage during experimentally induced restraint stress in Wistar albino rats with respect to changes in the levels of lipid peroxidation, antioxidant status (GST, GPx, CAT, SOD activities, and GSH level) in lymphoid organs of thymus and spleen, changes in the adrenal weight, plasma protein, and corticosterone levels.…”
Section: Introductionmentioning
confidence: 94%
“…Calcium overload in myocardial cells during ischemia activates Ca 2+ -dependent ATPase in the membrane, which depletes high-energy phosphate stores and thereby indirectly inhibits Na + and K + transport and inactivates Na + -K + -ATPase [35]. This process is another important factor leading to myocardial oxidative damage and apoptosis [36,37,38]. Na + -K + -ATPase maintains an active potential and myocardial excitation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that betaine regulates erythrocyte (red blood cell) membrane ATPases via conformational changes, which results in cell volume control (Moeckel et al 2002). Earlier, we reported the protective effect of betaine on antioxidant status (Ganesan et al 2008b), mitochondrial function (Ganesan et al 2007a), protein and glycoprotein metabolism (Ganesan et al 2007b), and lipid metabolism (Ganesan et al 2008a) in isoprenaline-induced myocardial infarction in Wistar rats. In the present study, an attempt was made to assess the protective effects of betaine on isoprenaline-induced myocardial infarction with respect to changes in the levels of lysosomal enzymes and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 93%